Zastoji pravdnega postopka zaradi razlogov na strani pravne osebe - Klun, Gregor (Podjetje in delo, 2014)
The article deals with issues regarding the interruption of civil proceedings due to events concerning legal persons. The topic is much wider than what is relatively scarcely regulated under Chapter XVII of the Slovenian Civil Procedure Act. This is so because it goes to the heart of some of the fundamental institutions of substantive and procedural law. The author aims at presenting concisely some of these issues, and to expose some of the dilemmas over which the statutory rules do not give (clear) answers.
Keywords: gospodarske družbe; pravdni postopek; pravne osebe; procesno pravo